PKM KELOMPOK NELAYAN BERESIKO MASALAH KESEHATAN DI KAMPUNG PALARENG KECAMATAN TABUKAN SELATAN PROVINSI SULAWESI UTARA - Iswanto Gobel; Meistvin Welembuntu; Christien A. Rambi; Elviera Tumbale; Fitria Soleman (Jurnal Ilmiah Tatengkorang, 2018)
Palareng village is located in Tabukan Selatan district, Regency of Sangihe Island, North Sulawesi Province. Based on the Geographical location, this Palareng village is a land located in Sangihe Archipelago but because there is no connecting road between Palareng and the city of Tabukan Selatan , in order we can visit this village we have use the small boat and the said village can be reached within 20 minutes if the weather and the ocean are good. If the water recedes then the boat can not lean to the village, the passengers have to go down on the neighboring beach that can be tie up and take the land route as far as 100 meters from the village. Based on the preliminary research, majority the community of Palareng is fisherman, local people do diving activities for catching the fish in traditional way, namely “Memiti”. Based on the data from the society there were 2 victims who died because of barotrauma and decreased consciousness. There are 40 traditional divers in this village. The method used to overcame the problems of the partners were the training that given the knowledge about health problems due to diving activities for the fisherman. After the training the knowledge of the participants has 70 persen increase and they knew the techique of Basic Life Support. Expected outcome of this program that the marine accidents will decrease and death will be avoided.